2022
DOI: 10.1155/2022/4987929
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of Antioxidants Activity of Indigenously Produced Moringa Oleifera Seeds Extracts

Abstract: Medicinal plants are used to control and remediate oxidative stress related diseases caused by free radicals. Thus, these plants find their use as remedy. Moringa oleifera is an extremely valued plant for its medicinal properties. Herein, two indigenously produced accessions of Moringa oleifera seeds [originated from Multan (M-Mln) and India (PKM1)] were investigated for their antioxidant properties by 2.2-Diphenyl-1picrylhydrazyl (DPPH) assay, total phenolics content and total flavonoids content. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…While the standard antioxidant had an IC50 of 127.737 μg/ml. Low IC 50 values correspond to high antioxidant activity [ 52 ]. Thus, the EtOH extract had the highest antioxidant activity among the other leaves extract which has the smallest IC50 value at higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…While the standard antioxidant had an IC50 of 127.737 μg/ml. Low IC 50 values correspond to high antioxidant activity [ 52 ]. Thus, the EtOH extract had the highest antioxidant activity among the other leaves extract which has the smallest IC50 value at higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…40 The antioxidant activity of the three solvents extracts, DHCL and ascorbic acid against DPPH assay was tested with concentrations ranging from 50 to 300 μg/mL as the results shown in Table 4. As shown in 41 Thus, pure isolated DHCL had the highest antioxidant activity compared with crude extracts and EtOH extract showed higher inhibitory activity among the other root extracts. From these results, it was also possible to make several correlations regarding the relationship between the structure of isolated compound DHCL and its DPPH-scavenging activities.…”
Section: Antioxidant Activitymentioning
confidence: 69%
“…The IC50 values of DPPH assay for the hexane, EtOAc, MeOH, and DHCL were 109.70, 95.34, 94.71, and 93.10, respectively, as compared with standard AA 91.82. Low IC50 values correspond to high antioxidant activity 41 …”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%